Sustainable achievement of selective KPIs of different players in education: an update for policy discourse and role of tertiary education - Alam, Gazi Mahabubul; Forhad, Abdur Rahman (Inderscience, 2022)
Key performance indicator (KPI) has become a fundamental part of evaluation that focuses on either an individual or a system. Setting KPIs and their revisions is a continuous process that is often determined through either an agreeable or a heated discussion. This paper is the first to investigate the achievement of KPIs of different players in education using Bangladesh as a case study. Because of the nature of policy discourse research, secondary data are used from the designated agencies. Increasing enrolment with the assurance of high-quality education was determined as the prime KPI for primary/secondary provisions. Quantitative KPIs are achieved, which is unsustainable. Both public and private sectors are players in tertiary education; none of them accomplish the prime KPI setup, which consists of research. The need to supply 'job-ready graduates' is ignored. This study suggests that new policy must be formed to attain a sustainable achievement of KPIs.